JOURNAL OF GOVERNMENT & POLITICS : The indonesia's Police Reform Police in the Reform Era New Institutionalism Perspective - Achmad Nurmandi , Isnaini Muallidin (FISIPOL UMY, 2016)
Since the reformation and democratization movement in 1998, Indonesians have faced a chronic corruption problem.